Plurality in the Capital: The Christian Responses to London’s Religious Minorities since 1800 - Wolffe, John (Studies in church history, 2015)
On a late spring day in 1856 Prince Albert carried out one of the less routine royal engagements of the Victorian era, by laying the foundation stone of what was to become ‘The Strangers’ Home for Asiatics, Africans and South Sea Islanders’, located at Limehouse in the London docklands. The deputation receiving the prince was headed by the earl of Chichester, who was the First Church Estates Commissioner and president of the Church Missionary Society, and included Thomas Carr, formerly bishop of Bombay, Maharajah Duleep Singh, a Sikh convert to Christianity and a favourite of Queen Victoria, and William Henry Sykes, MP and chairman of the East India Company.